The Flight Pattern of Navel Orangeworm (Amyelois transitella Walker) 2008–2023 in California Pistachio - Joel Philip Siegel (Insects)
The navel orangeworm, Amyelois transitella, is the principal pest of pistachio and almond in California. The timing of the insecticide application is challenging because there is no model that predicts when pistachio is vulnerable to infestation. Sixteen years of pistachio flight data from Madera and Fresno counties (541,892 adults) were analyzed to determine if there was a consistent starting point each year for flights that overlap pistachio vulnerability. This effort was complicated by changes in trap lures over this period, as unmated females were replaced by a combination lure consisting of the synthetic pheromone and phenyl propionate, which is needed because mating disruption suppresses pheromone lure trap capture. There were two additional complications: the increased degree day accumulation during the growing season and the three-fold hectarage expansion of pistachio. A biofix at 944.4 degree days °C from the beginning of the year was identified from the dataset, which was consistent across all years in both counties. Using the biofix, subsequent flight peaks occurred at 277.78 degree day °C intervals (generation time on new crop pistachios), corresponding to three weeks in the field. This biofix can be used to improve the timing of field scouting, which in turn will improve the timing of insecticide application.